Public sector efficiency in Europe: Long-run trends, recent developments and determinants - Michael Christl; Monika Köppl-Turyna; Dénes Kucsera (Agenda Austria, 2018)
This paper investigates the efficiency of the public sector in a sense of public performance and expenditures. For 23 European countries and for the period between 1995 and 2015 we construct a measure of public sector performance that consist of nine distinct indices for each area of public policy, such as administration, health education, economic performance, security and infrastructure. We use several efficiency techniques (FDH, order-m) and investigate input- and output-oriented efficiency of the public sector. We find that countries with small public sectors tend to be more efficient no matter which efficiency techniques we use. Because of the relatively long time span of our data, our study contributes to the literature by analyzing the effect of the financial crisis on the efficiency of the public sector in European countries. We show that after the crisis, the public sector efficiency increased especially in countries with small public sectors, while it stayed constant or worsened in countries with big public sectors. Finally, we analyze in more depth the impact of fiscal decentralization and fiscal rules on the public sector efficiency. We conclude that while decentralization is fostering efficiency, fiscal rules do not have any effect. Moreover, fiscal rules combined with decentralization may harm efficiency, consistently with the ratchet effect.
Keywords: C14; H50; H72; 330; public sector; efficiency; order-m; input-oriented efficiency; output-oriented efficiency; decentralization; fiscal rules